2017
DOI: 10.15171/joddd.2017.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retreatment on the push-out bond strength of MTAbased and epoxy resin-based endodontic sealers

Abstract: Background. Further studies on the adhesion properties of MTA-based materials seem necessary due to their growing use in endodontic treatment. This research aimed to assess the effect of retreatment on the bond strength of MTA-based (MTA Fillapex) and epoxy resin-based (AH Plus) sealers.Methods. ProTaper rotary files were applied to prepare the root canals of 80 human mandibular premolars. Then, the roots were randomly divided intotwo groups of A (n=40) and B (n=40), which were obturated with gutta-percha and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
7
2
Order By: Relevance
“…The present study showed that, any of the EndoSequence BC specimens revealed cohesive bond failure which in contrast to [42] who inspected samples filled with gutta percha/ AH Plus and gutta-percha/ EndoSequence BC Sealer and found that, the type of bond failure was mainly cohesive for all groups.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The present study showed that, any of the EndoSequence BC specimens revealed cohesive bond failure which in contrast to [42] who inspected samples filled with gutta percha/ AH Plus and gutta-percha/ EndoSequence BC Sealer and found that, the type of bond failure was mainly cohesive for all groups.…”
Section: Discussioncontrasting
confidence: 95%
“…But, this result was in contrast to Koch and Brave (2009) [52] who stated that, in most studies, Endosequence sealer were equivalent to epoxy resin-based sealers, which are known by its excellent bonding properties [53] . Also, this result was in disagreement with [42] who found no significant difference between the bond strength of gutta percha/ AH Plus (epoxy resin-based) and gutta-percha/EndoSequence BC Sealer.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This method is very useful in testing the adhesion of root canal sealers and retention of posts luted in root canals [ 15 ]. The PO test is based on generating shear stress at the interface between dentin and cement, as well as between post and cement [ 16 ]. When the PO test is used to test bond strength of adhesives to dentin, a 1 to 2 mm thick dentin slice is punched to produce a tapered cylindrical hole.…”
Section: Types Of Bond Strength Testing Methodsmentioning
confidence: 99%
“…The multiple test panels for measuring the bond strength are push-out, shear, and micro tensile strength tests. A study by Goracci et al concluded that the push-out test is very reliable as this method gives a clear clinical picture in determining the binding efficiency of the root canal sealer [ 11 ]. Therefore, we chose this method in our study.…”
Section: Discussionmentioning
confidence: 99%